Common consequence effects with pricing data - Schmidt, Ulrich; Trautmann, Stefan T. (Kiel working paper, 2010)
This paper presents an experimental study analyzing common consequence effects with binary choice, willingness-to-pay (WTP), and willingness-to-accept (WTA). Consistent with previous research we do not find clearcut evidence of fanning out in the absence of certainty effects. Violation rates of EU are more pronounced for WTP and WTA than for choice data. Moreover, there is a strong tendency for violations in the direction of fanning out. Our results reinforce the significance of common consequence effects and provide support for the operation of cancellation in prospect theory. -- Common consequence effects ; fanning out ; WTP ; WTA ; cancellation